2017
DOI: 10.1038/s41598-017-15456-9
|View full text |Cite
|
Sign up to set email alerts
|

The positive effects of Xueshuan Xinmai tablets on brain functional connectivity in acute ischemic stroke: a placebo controlled randomized trial

Abstract: Through a placebo controlled randomized study, the purpose of this report was to investigate the effects of Xueshuan Xinmai tablets (XXMT) on neurologic deficits, quality of life and brain functional connectivity in acute ischemic stroke patients and to explore the mechanism of action of XXMT. In total, 44 acute ischemic stroke patients were randomly divided to the XXMT treatment group (n = 22) or the placebo group (n = 22) in a 2-week trial. Before and after the treatment, the neurological assessment and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(28 reference statements)
0
1
0
1
Order By: Relevance
“…It mainly includes two kinds of active components, namely water‐soluble salvianolic acids and lipophilic Tanshinones (Jung, Kim, Moon, Lee, & Kim, 2020). Among them, TanIIA is the most abundant and well‐studied active ingredient that possesses anti‐inflammatory, antioxidant, antiapoptotic, and neuroprotective properties (Wei et al, 2017). However, the effect of TanIIA on central nervous system (CNS) is not well known although it has been reported that TanIIA can improve learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…It mainly includes two kinds of active components, namely water‐soluble salvianolic acids and lipophilic Tanshinones (Jung, Kim, Moon, Lee, & Kim, 2020). Among them, TanIIA is the most abundant and well‐studied active ingredient that possesses anti‐inflammatory, antioxidant, antiapoptotic, and neuroprotective properties (Wei et al, 2017). However, the effect of TanIIA on central nervous system (CNS) is not well known although it has been reported that TanIIA can improve learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, poderão ser levantados àqueles que poderão impactar na capacidade funcional desses indivíduos para a realização das atividades de autocuidado. (56,57) De forma similar ao realizado pelo Center for Nursing Classification and Clinical Effectiveness de Iowa que testou a praticabilidade de uma lista de RE com enfermeiros da prática clínica, neste estudo, a segunda etapa de validação do Estado neurológica contemplou a avaliação da relevância dos seus indicadores para os pacientes com AVC. (10) Ao se construir ou validar instrumentos/escalas é importante verificar a consistências de seus itens com o constructo estudado.…”
Section: Discussão Geralunclassified